Reduced bone mineral density in human immunodeficiency virus-infected individuals: a meta-analysis of its prevalence and risk factors - Goh, S.S.L.; Lai, Pauline Siew Mei; Tan, Alexander Tong Boon; Ponnampalavanar, Sasheela (Springer, 2018)
Summary: A meta-analysis was conducted to evaluate the prevalence of osteopenia/osteoporosis in human immunodeficiency virus (HIV)-infected individuals. The prevalence of osteopenia/osteoporosis in HIV-infected and antiretroviral therapy (ART)-treated individuals was significantly higher than respective controls. Evidence regarding bone loss within first year of HIV infection or ART initiation was preliminary. Purpose: The aim of the study is to systematically review published literature on the prevalence of osteopenia/osteoporosis and its associated risk factors in HIV-infected individuals. Methods: A literature search was conducted from 1989 to 2015 in six databases. Full text, English articles on HIV-infected individuals ≥ 18 years, which used dual X-ray absorptiometry to measure BMD, were included. Studies were excluded if the prevalence of osteopenia/osteoporosis was without a comparison group, and the BMD/T-score were not reported. Results: Twenty-one cross sectional and eight longitudinal studies were included. The prevalence of osteopenia/osteoporosis was significantly higher in both HIV-infected [odds ratio (OR) = 2.4 (95%Cl: 2.0, 2.8) at lumbar spine, 2.6 (95%Cl: 2.2, 3.0) at hip] and ART-treated individuals [OR = 2.8 (95%Cl: 2.0, 3.8) at lumbar spine, 3.4 (95%Cl: 2.5, 4.7) at hip] when compared to controls. PI-treated individuals had an OR of 1.3 (95%Cl: 1.0, 1.7) of developing osteopenia/osteoporosis compared to controls. A higher proportion of tenofovir-treated individuals (52.6%) had lower BMD compared to controls (42.7%), but did not reach statistical significance (p = 0.248). No significant difference was found in the percent change of BMD at the lumbar spine, femoral neck, or total hip from baseline to follow-up between HIV-infected, PI-treated, tenofovir-treated, and controls. Older age, history of bone fracture, low BMI, low body weight, being Hispanic or Caucasian, low testosterone level, smoking, low CD4 cell count, lipodystrophy, low fat mass, and low lean body mass were associated with low BMD. Conclusions: The prevalence of osteopenia/osteoporosis in HIV-infected and antiretroviral therapy (ART)-treated individuals was two times more compared to controls. However, evidence concerning bone loss within the first year of HIV infection and ART initiation was preliminary.